Perioperative blood glucose variability and autonomic nervous system activity in on-pump cardiac surgery patients: Study protocol of a single-center observational study. Issue 47 (25th November 2022) - Chazal, Etienne; Parmentier, Anne-Laure; Pili-Floury, Sebastien; Bouhaddi, Malika; Borot, Sophie; Perrotti, Andrea; Vettoretti, Lucie; Trajkovski, Julian; Ferreira, David; Zanoni, Chloe; Samain, Emmanuel; Besch, Guillaume; et al.
Abstract : Introduction: On-pump coronary artery bypass graft (CABG) and surgical valve replacement (SVR) are high-risk procedures. Several studies reported that perioperative blood glucose (BG) variability was independently associated with impaired postoperative outcome. However, the underlying mechanisms contributing to increased perioperative BG variability and to its deleterious impact remain unknown. The hypothesis of the study is that perioperative BG variability could be related to perioperative alteration of the autonomic nervous system (ANS) activity and to preoperative BG variability. Methods and analysis: We designed a prospective observational single-center study. Four groups of 30 patients will be studied: group 1, including insulin-requiring type 2 diabetic patients undergoing on-pump CABG; group 2, including non-insulin-requiring type 2 diabetic patients undergoing on-pump CABG; group 3, including non-diabetic patients undergoing aortic SVR; and group 4, including non-diabetic patient undergoing on-pump CABG. Preoperative (baseline) and postoperative BG variability will be quantified using the Abbott's Freestyle Libre Pro sensor allowing for continuous subcutaneous BG monitoring. Preoperative (baseline) and postoperative ANS activity will be measured using noninvasive continuous heart rate monitoring (Mooky HR memory®). Blood level and urinary concentration of inflammatory and endothelial dysfunction biomarkers will be measured from blood and urinary samples at the end of the surgery and on postoperative day 1 and 2. The primary objective is to describe the relationship between baseline BG variability and postoperative BG variability. The secondary objectives are to describe the relationship: between baseline and postoperative BG variability according to the diabetes phenotype and to the type of surgery; between the ANS activity and the BG variability; and between postoperative BG variability and, urinary and blood biomarkers.